Conservation of water resources in the United Kingdom proceedings of the symposium organised by, and held at, the Institution of Civil Engineers on 30 and 31 October and 1 November 1962. (Institution of Civil Engineers, 1963)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a symposium held on 30 Oct-1 Nov 1962.